Orchestrating Lymphocyte Polarity in Cognate Immune Cell–Cell Interactions - Bustos-Morán, Eugenio (Int Rev Cell Mol Biol, 2016)
The immune synapse (IS) is a specialized structure established between different immune cells that fulfills several functions, including a role as a communication bridge. This intimate contact between a T cell and an antigen-presenting cell promotes the proliferation and differentiation of lymphocytes involved in the contact. T-cell activation requires the specific triggering of the T-cell receptor (TCR), which promotes the activation of different signaling pathways inducing the polarization of the T cell. During this process, different adhesion and signaling receptors reorganize at specialized membrane domains, concomitantly to the polarization of the tubulin and actin cytoskeletons, forming stable polarization platforms. The centrosome also moves toward the IS, driving the movement of different organelles, such as the biosynthetic, secretory, degrading machinery, and mitochondria, to sustain T-cell activation. A proper orchestration of all these events is essential for T-cell effector functions and the accomplishment of a complete immune response.